Synthesis and application of Cobalt-Silver nanohybrid for antimicrobial wastewater treatment and agricultural productivity enhancement - Sayed M. S. Abo El-Souad; Marwa A. Ramadan; D. Zahran (Scientific Reports)
Abstract 1- This work emphasises the potential of Co@Ag-NPs as an efficient antimicrobial agent. The scientific community has recently shown silver nanohybrids to maintain plural consistency and their potential applications in wastewater treatment. Where these nanohybrids showed highly removing capacity of the three main contaminants (pesticides, microorganisms, and heavy metals) from waste water. The ability of silver and cobalt nanohybrids to inhibit bacteria and fungi that cause illnesses both in vitro and in vivo has made them an outstanding antimicrobial agent. Cobalt-silver nanohybrid particles (Co@AgNPs) have antibacterial properties against both Gram-positive and Gram-negative bacteria, including those that are resistant to multiple drugs. Co@AgNPs have several simultaneous modes of action, and when combined with organic chemicals or medicines that fight bacteria, they have demonstrated a synergistic effect on infections. Because of their unique properties, silver and cobalt nanohybrids can be used in medical and healthcare goods to effectively treat or prevent infections. The preparation and characterization of highly stable cobalt silver nanohybrid (Co@Ag) have been reported. Out of the water samples, four bacterial and seven fungal isolates are identified. Various concentrations of Co@Ag, ranging from 10− 1 to 10− 3, have been seen to impact and produce varying diameters of inhibition zones in bacterial isolates Shigella, Salmonella, E. coli, Pseudomonas aeruginosa and fungal isolates Aspergillus flavus var columnaris, and Aspergillus awamori. Water samples treated with Co@Ag nanoparticles when plated on LB and Czapek Dox agar did not show any growth of bacteria and fungi after five and seven days of incubation, respectively. Furthermore, data demonstrated that shoot and root length and germination percentage of wheat seeds irrigated by treated water increased progressively from 7.5 cm to 9.2 cm, from 9 cm to 11 cm and from 90 to 100%, respectively, as Co@Ag concentrations were elevated from 0 to 10 and 20 mg/l.